Nursing Therapy in Dealing with Anxiety of COVID-19 Patients Based on the Model of Interspersonal Relations of Hildegard Peplau - Edmelyn Babas Cacayan; Angelito Estoesta Alvarado; Oliver A. Esmundo; Alona Dela Cruz; Federick Chy Felix; Dencel Franco; Jesalie Mae Diaz Galima (Health Notions, 2021)
The rising incidence of COVID-19 positive affects the everyday life of everyone. Anxiety among the COVID-19 positive is one of the concerns of nurses because they are the one who are caring and dealing with those infected patients. The purpose of this study is to determine the nursing therapy in dealing with anxiety of COVID-19 patients, based on Interpersonal Relation’s Theory of Hildegard Peplau that consists of four phases (orientation, identification, exploitation and resolution) which served as the guide to assess accurately the actions and techniques of nurses in dealing with anxiety of COVID-19 patients. Qualitative descriptive research design was utilized in this study to have a deeper understanding to the techniques provided by nurses in dealing with their patients. Researchers used a non-probability sampling technique, specifically referred sampling in choosing the 20 participants wherein they must handle COVID-19 positive patients and had attended trainings regarding mental health. A written interview questionnaire was disseminated to the participants to gather necessary data for this study. The statistical measure and analysis used in this study were frequency and percentage for participant’s profile and thematic analysis for open-ended questions to compile, categories and look for patterns of data to help the researchers generate themes to assert the different nursing therapy in dealing with patients experiencing anxiety. Through the guide of Hildegard Peplau’s Theory researchers found out eight themes; identifying anxiety techniques, interaction time, interview techniques, therapeutic communication techniques, relaxation techniques, attitude/behavior, therapeutic basis and health teaching. The findings of this study will serve as basis for nursing profession including nursing practice, nursing education, nursing research and clinical practice guidelines. Keywords: interpersonal relation theory; anxiety; COVID-19; Hildegard Peplau